Performance of the Afferent Limb of Rapid Response Systems in Managing Deteriorating Patients: A Systematic Review - Marcello Difonzo (Critical Care Research and Practice)
Introduction. The clinical components of the rapid response system (RRS) are the afferent limb, to ensure identification of in-hospital patients who deteriorate and activation of a response, and the efferent limb, to provide the response. This review aims to evaluate the factors that influence the performance of the afferent limb in managing deteriorating ward patients and their effects on patient outcomes. Methods. A systematic review was performed for the years 1995–2017 by employing five electronic databases. Articles were included assessing the ability of the ward staffs to monitor, recognize, and escalate care to patient deterioration. The findings were summarized using a narrative approach. Results. Thirty-one studies met the inclusion criteria. The analysis revealed major themes enclosing several factors affecting management of patients having sudden deterioration. The monitoring and recognition process was conditioned by the lack of recording of physiological parameters, the influence of facilitators, including staff education and training, and barriers, including human and environmental factors, and poor compliance with the calling criteria. The escalation of care process highlighted the influence of cultural barriers and personal judgment on RRS activation. Mainly, delayed team calls were factors strongly associated with the increased risk of unplanned admissions to the intensive care unit and length of stay, hospital length of stay and mortality, and 30-day mortality. Conclusions. A combination of factors affects the timely identification and response to sudden deterioration by general ward staffs, leading to suboptimal care of patients, delayed or failed activation of RRS teams, and increased risks of worsening outcomes. The research efforts and clinical involvement to improve the governance of the factors limiting the performance of the afferent limb may ensure proper management of hospitalized patients showing physiological deterioration.